Perbedaan Motivasi Berprestasi antara Siswa Reguler dengan Siswa Program Keluarga Harapan (PKH) - Lutviasari, Devvy; Setyowani, Ninik (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research has been implemented according to phenomenon in several elementary school state of Boja region which indicate the diversity between regular students and Conditional Cash Transfers (CCT) students. The objective of this research is to observe the difference of achievement motivation between regular students and CCT students. The population are 27 public elementary schools in Boja and the sample are 12 public elementary schools with 60 regular students and 60 CCT students using purposive sampling technique. The instrument has been tested for validity used product moment and reliability of the instrument with alpha formula. Data analysis techniques used that is analysis descriptive percentage. The researcher used statistical t-test analysis technique to analyze the data. The result showed significant number at 0,618. Based result t-test of achievement motivation score tcount= 9,042> ttable= 1,980 or meaning Ha is accepted and Ho is rejected. The result of this research is that there is difference achievement motivation between regular students and CCT students. Therefore, teachers are expected to give support and guidance to regular students and conditional CCT students in order to increase the studentâs acievement motivation in a better way.